2004
DOI: 10.1016/j.orthres.2003.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of antimicrobial coated polyurethane sleeves for external fixation pins

Abstract: This study was conducted to assess the potential of gentamicin coated polyurethane sleeves to inhibit bacterial colonization on external fixation pins and wires. These antimicrobial sleeves have been designed to be fitted over the pins and wires, at the time of surgery, as a prophylactic approach to combat the major complication of external fixation treatment, pin tract infection. Elution testing was conducted to estimate the amount of gentamicin released into the pin tract. These gentamicin concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…These coatings successfully decreased the amount of bacteria surrounding the coated surfaces. Forster et al 16 found that using gentamicin-coated PU sleeves over external fixation pins inhibited bacterial colonization. Release kinetic experiments for these coatings showed an initial burst release, followed by a constant antibiotic release at a level above the minimal inhibitory concentration (MIC) for the antibiotics used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These coatings successfully decreased the amount of bacteria surrounding the coated surfaces. Forster et al 16 found that using gentamicin-coated PU sleeves over external fixation pins inhibited bacterial colonization. Release kinetic experiments for these coatings showed an initial burst release, followed by a constant antibiotic release at a level above the minimal inhibitory concentration (MIC) for the antibiotics used.…”
Section: Introductionmentioning
confidence: 99%
“…Release kinetic experiments for these coatings showed an initial burst release, followed by a constant antibiotic release at a level above the minimal inhibitory concentration (MIC) for the antibiotics used. [13][14][15][16] MIC values are useful, but the bactericidal activity in vivo is unpredictable due to host reactions. For example, in vitro methicillin resistant S. aureus (MRSA) and methicillin susceptible S. aureus (MSSA) are susceptible to a variety of antibiotics; however, in vivo MRSA and MSSA bacteria are less susceptible and show resistance to the antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Forster et al 31 in their study carried out to assess the potential of gentamicin coated polyurethane sleeves to inhibit bacterial colonization on external fixation pins and wires. The initial burst release was characterized by predicted pin tract gentamicin concentrations of >80 µg/ml at the 2 h and 1day elution time points.…”
Section: Discussionmentioning
confidence: 99%
“…They reported on the techniques, including loading the nanotubes with the antibiotic gentamicin. Another report described prevention of pin tract infection by fitting gentamicincoated sleeves over the pins [21]. These studies were basic research and not clinical trials.…”
Section: Discussionmentioning
confidence: 99%